CONSTRUCTING OF CONTENTS OF EDUCATIONAL DISCIPLINES FOR PREPARATION OF FUTURE ENGINEERS IN THE EDUCATIONAL INFORMATION ENVIRONMENT OF THE TECHNICAL UNIVERSITY - Рахманов, В. О.; Алпатова, О. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
The article identified and analyzed the features of the constructing content of educational disciplines to train future engineers in terms of educational information environment of the Technical University. This article presents the constructing stages of educational disciplines that include refined ideas of creating educational process. The proposed approaches to designing the content of educational disciplines enable effectively development of independence and consciousness in choosing of the desired level and accessible education, improvement of education quality, objective determining of the level of future engineers training and also specify them ways to further knowledge improvement